FO-BASED INTEGRATED SYSTEM FOR JUICE CONCENTRATION : SYSTEM DESIGN AND EXPERIMENTAL INVESTIGATION - Muhammad Maulidi Surur Fahmi; Wang Qun (DISTILAT: Jurnal Teknologi Separasi, 2025)
Fruit juices are concentrated using traditional methods such as dual stage vacuum evaporation. The impact of this method is to reduce the colour, eliminate the taste of fresh fruit juice, and have an unpleasant taste. In addition, the simultaneous concentration of fruit juices and preservation of nutritional and thermosensitive components poses challenges in food processing. Membrane-based treatments are a promising alternative to fruit juice concentrates. The technology of forward osmosis (FO) has garnered increasing research interest for its excellent advantages in producing high-quality concentrated juice. This work investigated a double-stage, double-cycle FO system for fruit juice concentration, examining membrane type and draw solution combinations to optimize the process. Several additives and fertilizer containing high-valence ions were evaluated to improve the feasibility of the FO process for juice concentration, using nanofiltration (NF)-like and reverse osmosis (RO)-like FO membrane with an interlayer constructed by MOF-s based nanoparticles. The prepared NF-like and RO-like FO membranes exhibited negative potential, superior hydrophilicity, and uneven crosslinking, which matched well with one selected additive (MgSO4) and complex fertilizer (KCl, KH2PO4, NH4(H2PO4). Food additives and KH2PO4 fertilizers containing high valence negative ions are used, these properties can increase water transport. Double fertilizer is used in the draw solution, it is better to use KCL+NH4(H2PO4). Using a draw solution with triple fertilizer has more complete results compared to a draw solution with double fertilizer. Apart from that, the water flux value produced by the draw solution with triple fertilizer produces a small value.